Effects of pressure on the phase transformations and mechanical properties of 10 mol% Mg-PSZ sintered by HPHT. Issue 4 (6th January 2022) - Wang, Jian; Wang, Zhiwen; Wang, Yongkui; Ma, Hongan; Fang, Shuai; Chen, Qi; Wang, Yao; Wang, Chunxiao; Chen, Liangchao; Jia, Xiaopeng
Abstract : MgO (10 mol%)-stabilized zirconia ceramics were obtained using high-pressure high-temperature (HPHT) sintering. Abstract : MgO (10 mol%)-stabilized zirconia ceramics were obtained using high-pressure high-temperature (HPHT) sintering. The effects of the sintering pressure (2.5, 3.7, and 5.0 GPa) on the phase transformations and hardness were studied. The results showed that increasing the pressure during sintering suppressed the sintering of zirconia. Under a sintering pressure of 5 GPa, the temperature at which the sample completely transforms into the (t + c)-phase is 1930 °C, which is higher than 2.5 GPa. Upon increasing the sintering pressure, the hardness of the sample increased, and when the sintering pressure reached 5.0 GPa, the Vickers hardness reached the maximum of 15.8 GPa; however, the brittleness of the sample increased and its toughness decreased sharply. This was because, at a high pressure, a large number of defects such as lattice distortions and dislocations were introduced, which produced residual stress at grain boundaries and decreased the tetragonal phase content.